Plato and the individual - "Rankin, H.D." (London, 1964)
This sociological portrait presents the career of the individual human being within the context of Plato's social thought. For this purpose it considers Plato's treatment of the principal crises in an individual life: birth, educational selection section, sex, the individual's contract with society, old age. death and life after death.
Keywords: Sociology